"The Perfection of Democracy Cannot Dispense with Dealing with the Past:" Dictatorship, Memory, and the Politics of the Present in Brazil. Issue 1 (20th April 2018) - Snider, Colin M.
Abstract: This article uses recent events in Brazil to argue for a consideration of the ways collective memory and transitional politics intersect with political life in the twenty‐first century. Drawing on a wide array of phenomena – the creation and completion of Brazil's National Truth Commission, the 2013 protests, the 2016 impeachment of Dilma Rousseff, and more – this article considers the ways in which the military past continues to ripple into the present at the discursive, political, and social levels. In the process, I argue for an expanded approach to transitional politics that explores the ways in which memories, discourses, and policies from military regimes continue to shape politics, society, and discourse decades after militaries left power not just in Brazil, but throughout South America.